1992
DOI: 10.1177/019874299201800101
|View full text |Cite
|
Sign up to set email alerts
|

Aggression Replacement Training with Behaviorally Disordered Adolescents

Abstract: This study assessed the effects of a 10-week aggression replacement training program with a group of 39 adolescents with behavioral disorders in residential treatment. Two-thirds of the sample had DSM III-R diagnoses of conduct disorder. Assigned to the treatment group were 25 subjects and 14 subjects were assigned to the control group. Subjects were pre- and posttested on four criterion-referenced measures and one behavior incident measure. Personality characteristics of subjects reflecting possible amenabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…Randomized controlled trials. Coleman et al (1992) found no significant differences between the ART condition and the control condition in acting-out behavior self-control, social skills and moral reasoning, see Table 1. In Jones (1991), three conditions were compared: ART, the moral-reasoning component of ART only, and a treatment-as-usual (TAU) control.…”
Section: Effects On Anger Control Social Skills and Moral Reasoningmentioning
confidence: 84%
See 3 more Smart Citations
“…Randomized controlled trials. Coleman et al (1992) found no significant differences between the ART condition and the control condition in acting-out behavior self-control, social skills and moral reasoning, see Table 1. In Jones (1991), three conditions were compared: ART, the moral-reasoning component of ART only, and a treatment-as-usual (TAU) control.…”
Section: Effects On Anger Control Social Skills and Moral Reasoningmentioning
confidence: 84%
“…In eleven of the 16 included studies, it was unclear how many of the participants had a history of aggressive-, violent-and/or criminal behavior although the general statements made by the investigators suggest that at least some participants had such a history. A history of drug/alcohol abuse was reported in four studies (Barnoski, 2004;Coleman, Pfeiffer, & Oakland (1992); Danielsson et al, 2011;Erickson, 2013). The remaining twelve studies did not provide any information on the drug/alcohol abuse histories of the participants.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Homogeneity of samples and a lack of reporting on ethnicity in early research threaten the external validity of past findings. For example, three samples consisted of predominantly white males (Kennedy, 1989;Curulla, 1991;Leeman et al, 1993), racial demographic data were not available in other studies (Goldstein et al, 1989;Jones, 1991;Coleman et al, 1992;Gundersen & Svartdal, 2006), and only four experimental ART studies included multiethnic samples (Goldstein et al, 1987(Goldstein et al, , 1994Nodarse 1998;Nugent et al, 1999). Given that minorities are overrepresented compared to whites in the delinquent population (Glick, 2003) this shortcoming limits consumers' ability to comprehend findings' implications or replicate findings (Dowden, Antonowicz & Andrews, 2003).…”
Section: Limitations In Existent Researchmentioning
confidence: 99%